The flint community school program, an overview - Bates, Guy J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1963)
The public elementary school had become the ideal center for community education in flint. It was the practical place for carrying the constantly changing activities and programs of the community. The approach used to facilitate human understanding and interaction included, first, getting the people into the schools, where they became interested. Next they became involved in school-community affairs and activities, and finally, as responsible citizens, they became informed about local issues and community problems. Some of the programs described included the community recreation program which involved baseball, basketball, football, and gymnastics. Also described were the programs serving youth, including the mott camp, clubs for teenage girls, and the big brother program.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Schools; Elementary Schools; School Community Relationship; Special Programs; Youth Programs; Michigan -- Michigan (Flint)